APPLYING THE PYTHON PROGRAMMING LANGUAGE AND ARDUINO ROBOTICS KITS IN THE PROCESS OF TRAINING FUTURE TEACHERS OF COMPUTER SCIENCE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article explores the possibilities and advantages of applying the Python programming language for using Arduino robotics kits in the process of training future computer science teachers in pedagogical institutions of education. Considerable emphasis is placed on analyzing the principles of operation of simple programs and devices. This analysis visualizes the possibilities of using the Arduino platform and Python libraries to create robots that can be implemented in education and everyday life. The authors have presented a working model of a robot built and programmed on the basis of Arduino components to measure humidity in computer laboratories and develop automatic plant irrigation systems to maintain appropriate conditions in classrooms. They also provide an example of integrating the learning of the Python programming language with the use of Arduino robotics kits. This method aims to enhance the quality of training for future computer science teachers, broaden their methodological toolkit, and equip them with the ability to teach students using innovative methods. The study's results and the developed teaching materials aim to increase students' interest in STEM education and prepare a new generation of computer science teachers for the challenges of the modern technological world. This will expand their methodological arsenal and develop their ability to use integrated technical, engineering, and mathematical solutions to solve theoretical and practical problems. This study can serve as a guide for popularizing the use of Arduino and Python in educational institutions. It may encourage future computer science teachers to introduce STEM and practical teaching methods, which can contribute to better student learning and improve the quality of professional education in the field of information technology. The study presents opportunities for utilizing modern digital technologies in vocational education and encourages interest in STEM education among computer science teachers and students. This contributes to the development of a new generation of engineers and technology leaders. Further research could focus on developing targeted training courses and methods for integrating the Python programming language and Arduino robotics kits into STEM education. It is crucial to create interdisciplinary STEM courses with the involvement of computer science, physics, mathematics, and vocational education teachers in the IT industry.